The Influence of Work Motivation and Work Discipline on Employee Performance at the Wajo Regency Land Office - Siardin Andi Djemma; Ahmad Muktamar; Andi Bakti; Nurul Fajri (International Journal of Management Research and Economics, 2023)
The Wajo Regency Land Office is a government agency that operates in the field of services at the Wajo Regency National Land Agency. In order to carry out the agency's duties and functions well, human resources are needed who are able to work optimally. This research is quantitative research. The aim of this research is to analyze the influence of work motivation and work discipline on employee performance. The data analysis method used is multiple linear regression. All statements are valid, reliable and normal. The findings of this research are as follows: Based on the results of the t test on work motivation, it was obtained that the t count was 3.169 > t table of 2.101 and the significance was 0.004 < 0.05, so Ho was rejected and Ha was accepted, meaning that work motivation partially influences employee performance. The results of the t test on work discipline obtained t count of 2.249 > t table of 2.101 and a significance of 0.033 < 0.05, so Ho was rejected and Ha was accepted, meaning that work discipline partially influences employee performance. From the results of this research, it is known that employee performance at the Wajo Regency Land Office is influenced by work motivation and work discipline. And the advice that the author can give to employees at the Wajo Regency Land Office is to improve employee performance better than before.